Case Study: Supplementation of cow-calf pairs grazing smooth bromegrass pastures with ethanol by-products and low-quality forages - Warner, J.M. (Prof Anim Sci, 2017)
Multiparous, lactating, crossbred (Simmental × Angus) beef cows with spring-born calves at side (n = 16 per year; 4 per pasture) were used each of 3 yr to evaluate supplementing modified distillers grains plus solubles mixed with low-quality forage on cow and calf performance while grazing. Cow-calf pairs were assigned randomly to treatment with 2 replications (pasture) per year for 3 yr. Treatments were (1) recommended stocking rate of 9.46 animal-unit month/ha with no supplementation (CON) or (2) double the recommended stocking rate (18.9 animal-unit month/ha) and supplemented with a 30:70 modified distillers grains plus solubles:cornstalks (DM) mixture (SUPP). To replace 50% of grazed forage DMI, SUPP pairs were fed an average of 1.13% of BW (DM) over the grazing season. Pairs grazed adjacent smooth bromegrass pastures for 130 d during the summer. Gain was not different (P = 0.19) between SUPP and CON cows (0.28 vs. 0.19 kg/d, respectively). Ending cow BW was not affected (P = 0.46) by treatment. Similarly, calf gain was not affected (P = 0.31) by supplementation. In studies where confined cow-calf pairs were fed average-quality (IVDMD = 52.9%) forage, DMI was 2.58% of pair BW. Based on these data, CON and SUPP pairs consumed 18.6 and 19.1 kg of DM, respectively, of total feed per pair daily. The SUPP pairs consumed 7.1 kg of DM/pair daily of the supplement, replacing approximately 35% of grazed forage intake. These data suggest mixtures of ethanol co-products and low-quality forages can be supplemented to replace grazed forage intake of cattle, allowing for increased stocking rate without affecting animal performance.